Solid-state mechanochemical ω-functionalization of poly(ethylene glycol) - Malca, Michael Y.; Ferko, Pierre-Olivier; Friščić, Tomislav; Moores, Audrey (Beilstein Journal of Organic Chemistry, 2017)
Poly(ethylene glycol) (PEG) is a linear polymer with a wide range of applications in chemical manufacturing, drug development and nanotechnology. PEG derivatives are being increasingly used to covalently modify small molecule and peptide drugs, as well as bioactive nanomaterials in order to improve solubility in biological serum, reduce immunogenicity, and enhance pharmacokinetic profiles. Herein we present the development of mechanochemical procedures for PEG functionalization without the need for bulk solvents, offering a cleaner and more sustainable alternative to existing solution-based PEG procedures. The herein presented mechanochemical procedures enable rapid and solvent-free derivatization of PEG with tosyl, bromide, thiol, carboxylic acid or amine functionalities in good to quantitative yields and with no polymer chain oligomerization, proving the versatility of the method.
Keywords: amination; bromination; carboxylation; mechanochemistry; poly(ethylene glycol); solid state; thiolation; tosylation

(untitled) - Li, J.; Kao, W. J. (Biomacromolecules, 2003)

(untitled) - Abuchowski, A.; Mccoy, J. R.; Palczuk, N. C.; Es, T. V. A. N.; Davis, F. F. (J. Biol. Chem., 1976)

(untitled) - Abuchowski, A.; Es, T. V.; Palczuk, N. C.; Davis, F. F. (J. Biol. Chem., 1977)

(untitled) - Gref, R.; Minamitake, Y.; Peracchia, M. T.; Trubetskoy, V.; Torchilin, V.; Langer, R. (Science, 1994)

(untitled) - Gref, R.; Domb, A.; Quellec, P.; Blunk, T.; Müller, R. H.; Verbavatz, J. M.; Langer, R. (Adv. Drug Delivery Rev., 1995)

(untitled) - Gref, R.; Lück, M.; Quellec, P.; Marchand, M.; Dellacherie, E.; Harnisch, S.; Blunk, T.; Müller, R. H. (Colloids Surf., B, 2000)

(untitled) - Li, W.; Zhan, P.; De Clercq, E.; Lou, H.; Liu, X. (Prog. Polym. Sci., 2013)

(untitled) - Juliano, R. L. (Adv. Drug Delivery Rev., 1988)

(untitled) - Stolnik, S.; Illum, L.; Davis, S. S. (Adv. Drug Delivery Rev., 1995)

(untitled) - Leroux, J.-C.; Allémann, E.; De Jaeghere, F.; Doelker, E.; Gurny, R. (J. Controlled Release, 1996)

(untitled) - Moghimi, M. S.; Hunter, C. A.; Murray, J. C. (Pharmacol. Rev., 2001)

(untitled) - Hrkach, J. S.; Peracchia, M. T.; Bomb, A.; Lotan, N.; Langer, R. (Biomaterials, 1997)

(untitled) - Klibanov, A. L.; Maruyama, K.; Beckerleg, A. M.; Torchilin, V. P.; Huang, L. (Biochim. Biophys. Acta, Biomembr., 1991)

(untitled) - Gombotz, W. R.; Guanghui, W.; Horbett, T. A.; Hoffman, A. S. (J. Biomed. Mater. Res., 1991)

(untitled) - Veronese, F. M.; Pasut, G. (Drug Discovery Today, 2005)

(untitled) - Na, H. B.; Lee, I. S.; Seo, H.; Park, Y. I.; Lee, J. H.; Kim, S.-W.; Hyeon, T. (Chem. Commun., 2007)

(untitled) - Gentili, D.; Ori, G.; Comes Franchini, M. (Chem. Commun., 2009)

(untitled) - Smolensky, E. D.; Park, H.-Y. E.; Berquó, T. S.; Pierre, V. C. (Contrast Media Mol. Imaging, 2011)

(untitled) - Thompson, M. S.; Vadala, T. P.; Vadala, M. L.; Lin, Y.; Riffle, J. S. (Polymer, 2008)

(untitled) - Mahou, R.; Wandrey, C. (Polymer, 2012)

(untitled) - Loiseau, F. A.; Hii, K. K.; Hill, A. M. (J. Org. Chem., 2004)

(untitled) - Dunn, P. J. (Chem. Soc. Rev., 2012)

(untitled) - Delori, A.; Friščić, T.; Jones, W. (CrystEngComm, 2012)

(untitled) - Bonnamour, J.; Métro, T.-X.; Martinez, J.; Lamaty, F. (Green Chem., 2013)

(untitled) - Tan, D.; Loots, L.; Friščić, T. (Chem. Commun., 2016)

(untitled) - Klok, H.-A.; Genzer, J. (ACS Macro Lett., 2015)

(untitled) - Ohn, N.; Shin, J.; Kim, S. S.; Kim, J. G. (ChemSusChem, 2017)

(untitled) - Ravnsbæk, J. B.; Swager, T. M. (ACS Macro Lett., 2014)

(untitled) - Jakobs, R. T. M.; Ma, S.; Sijbesma, R. P. (ACS Macro Lett., 2013)

(untitled) - Chen, X.; Yang, H.; Zhong, Z.; Yan, N. (Green Chem., 2017)

(untitled) - Friščić, T.; Jones, W. (Cryst. Growth Des., 2009)

(untitled) - Michalchuk, A. A. L.; Tumanov, I. A.; Konar, S.; Kimber, S. A. J.; Pulham, C. R.; Boldyreva, E. V. (Adv. Sci., 2017)

(untitled) - Karki, S.; Friščić, T.; Jones, W.; Motherwell, W. D. S. (Mol. Pharmaceutics, 2007)

(untitled) - Zhou, H.; Chen, Y.; Plummer, C. M.; Huang, H.; Chen, Y. (Polym. Chem., 2017)

(untitled) - Wang, J.; Sun, P.; Zheng, Z.; Wang, F.; Wang, X. (Polym. Degrad. Stab., 2012)

(untitled) - Xie, C.; Yang, C.; Zhang, P.; Zhang, J.; Wu, W.; Jiang, X. (Polym. Chem., 2015)

(untitled) - Liu, L.; Zhang, M.; Zhao, H. (Macromol. Rapid Commun., 2007)

(untitled) - Ishii, T.; Yamada, M.; Hirase, T.; Nagasaki, Y. (Polym. J., 2005)

(untitled) - Goswami, L. N.; Houston, Z. H.; Sarma, S. J.; Jalisatgi, S. S.; Hawthorne, M. F. (Org. Biomol. Chem., 2013)

(untitled) - Harris, J. M.; Struck, E. C.; Case, M. G.; Paley, M. S.; Yalpani, M.; Van Alstine, J. M.; Brooks, D. E. (J. Polym. Sci., Polym. Chem. Ed., 1984)